Video motion magnification for monitoring of vital signals using a perceptual model - Gomez-Coronel, Sandra L.; Brieva, Jorge; Moya-Albor, Ernesto; Ponce, Hiram (My University, 2017)
In this paper we present an Eulerian motion magnification technique using a spatial decomposition based on the Steered Hermite Transform (SHT) which is inspired in the Human Vision System (HVS). We test our method in one sequence of the breathing of a newborn baby and on a video sequence that shows the heartbeat on the wrist. We estimate the heart pulse applying the Fourier transform on the magnified sequences. Our motion magnification approach is compared to the Laplacian and the Cartesian Hermite decomposition strategies by means of quantitative metrics. © 2017 SPIE.